A systematic review and meta-analysis of almond effect on C-reactive protein and interleukin-6 in adults. (March 2023) - Hariri, Mitra; Amirkalali, Bahareh; Baradaran, Hamid Reza; Gholami, Ali
Abstract: Background: The previous articles have shown that the almond might reduce the serum concentration of inflammatory mediators. Therefore, the studies reported in this article aimed to assess the almond effect on serum concentration of C-reactive protein (CRP) and interleukin-6 (IL-6) in adults. Method and materials: To find the related English-language studies, an electronic search was run in databases including Web of Science, PubMed, SCOPUS, ClinicalTrials.gov, and Cochrane library with no time limit (up to August 2022). The effect sizes were calculated based on the mean changes for both intervention and comparison groups. DerSimonian and Laird random-effects model was used to determine the summary of overall effects and their heterogeneity. Cochran's Q test and I-squared statistic were used to explore the statistical heterogeneity. Results: In total, eleven studies were included in this study. The overall estimate indicated that the almond consumption had no significant effect on serum CRP level (weighted mean difference (WMD) = −0.28 mg/l, 95 % confidence interval (CI): − 0.81, 0.25; p = 0.29). Regarding IL-6, almond consumption significantly decreased serum IL-6 level (WMD = −0.1 pg/ml, 95 % CI: −0.15, −0.05; p < 0.001). Conclusion: The overall results support the beneficial effects of almond consumption on serum concentration of IL-6; but even so, our study revealed that the almond consumption non-significantly reduced serum concentration of CRP. We still need more well-designed trials to confirm the beneficial effects of almond. Highlights: The overall estimate indicated that almond consumption had no significant effect on serum C-reactive protein. Subgroup analysis revealed that almond consumption significantly decreased the serum C-reactive protein level in studies with duration < 84 day, at-risk participants, sample size ≥ 52, age< 58 years, and studies conducted in Europe. Regarding interleukin-6, almond consumption significantly decreased serum IL-6 level.